Altered Regional Brain Homogeneity of BOLD Signal in CADASIL: A Resting State fMRI Study. Issue 2 (13th December 2020) - Orsolini, Stefano; Marzi, Chiara; Gavazzi, Gioele; Bianchi, Andrea; Salvadori, Emilia; Giannelli, Marco; Donnini, Ida; Rinnoci, Valentina; Pescini, Francesca; Pantoni, Leonardo; Mascalchi, Mario; Diciotti, Stefano
ABSTRACT: BACKGROUND AND PURPOSE: The cognitive decline in cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is assumed to be due to a cortical‐subcortical disconnection secondary to damage to the cerebral white matter (WM). Using resting state functional MRI (rsfMRI) and analysis of the regional homogeneity (ReHo), we examined a group of CADASIL patients and a group of healthy subjects in order to: (1) explore possible differences between the two groups; and (2) to assess, in CADASIL patients, whether any ReHo abnormalities correlate with individual burdens of WM T2 ‐weighted hyperintensity and diffusion tensor imaging (DTI)‐derived index of mean diffusivity (MD) of the cerebral WM, an index reflecting microstructural damage in CADASIL. METHODS: Twenty‐three paucisymptomatic CADASIL patients (13 females; age mean ± standard deviation = 43.6 ± 11.1 years; three symptomatic and 20 with no or few symptoms) and 16 healthy controls (nine females; age 46.6 ± 11.0 years) were examined with T1 ‐weighted, T2 ‐weighted fluid attenuated inversion recovery images, DTI, and rsfMRI. RESULTS: When compared to controls, CADASIL patients showed four clusters of significantly lower ReHo values in cortical areas belonging to networks involved in inhibition and attention, including the right insula, the left superior frontal gyrus, and the bilateral anterior cingulated cortex. ReHo changes did not correlate with an individual patient's lesion burden or MD. CONCLUSIONS: This study reveals decreased ReHo of rsfMRI signals in cortical areas involved in inhibition and attention processes, suggesting a potential role for these functional cortical changes in CADASIL.